Harmonic mappings related to the convex functions - Yemişci, Halime Arzu; POLATOĞLU, YAŞAR (My University, 2014)
The main purpose of this paper is to give the extent idea which was introduced by R. M. Robinson [5]. One of the interesting application of this extent idea is an investigation of the class of harmonic mappings related to the convex functions.
Keywords: Harmonic Mappings; Distortion theorem; Growth theorem; Coefficient inequality